Kenali Kekasih Allah Courseware (KKA) / NurNajmina Roslee - Roslee, NurNajmina (2017)
Islamic Education lesson is one of the important aspects in the Integrated Curriculum for Primary and Secondary Schools in Malaysia. One of the topics in Islamic education is Sirah which is a study on the life of Prophet Muhammad S.A.W. Nowadays, the development of technology is changing the educational environment. Courseware is one of the additional tools that enhances teaching and learning environment. The development of a courseware is a proposed solution some issues that arise in teaching and learning of Islamic Education subjects. Kenali Kekasih Allah (KKA) Courseware is a courseware that is aimed at attracting students to learn more about Sirah Rasulullah which is, it has been integrated with five multimedia elements which are images, audio, text, animation and video. Furthermore, interactivity is added to enhance the learning process. KKA has been developed by using ADDIE model as a guideline. This model contains of five phases which are analysis, design, development, implement and evaluation. KKA courseware is being evaluated by three (3) experts and 30 potential users. The purpose of the evaluation is to evaluate the functionality and the usability of the KKA courseware. The evaluation construct is divided into six sections that evaluate the functionality and usability of KKA. The result of the evaluation shows that the respondent satisfied with the overall interface of the KKA courseware. Based on the finding results, it shows that the highest mean based on the user evaluation is on construct interface (Mean=4.433, SD=0.568). As a conclusion, KKA can attract students to learn about Sirah Rasulullah.